2019
DOI: 10.1111/acel.13020
|View full text |Cite
|
Sign up to set email alerts
|

Rag1 immunodeficiency‐induced early aging and senescence in zebrafish are dependent on chronic inflammation and oxidative stress

Abstract: In mammals, recombination activating gene 1 (RAG1) plays a crucial role in adaptive immunity, generating a vast range of immunoglobulins. Rag1−/− zebrafish (Danio rerio) are viable and reach adulthood without obvious signs of infectious disease in standard nonsterile conditions, suggesting that innate immunity could be enhanced to compensate for the lack of adaptive immunity. By using microarray analysis, we confirmed that the expression of immunity‐ and apoptosis‐related genes was increased in the rag1−/− fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 77 publications
(88 reference statements)
0
30
0
Order By: Relevance
“…In the case of crp genes, such compensatory effects might be due not only to their recently described antiviral activity [ 23 , 24 , 25 , 40 ] but also their evolutionary-conserved antibody-like activities [ 15 , 67 , 68 , 69 ]. In addition, the upregulation of this type of genes in rag1 −/− mutants has been associated with epigenetic reprogramming [ 70 ], similar to the underlying mechanisms regulating innate trained immunity [ 71 , 72 ], and apparently also occurring in the crp genes in zebrafish [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of crp genes, such compensatory effects might be due not only to their recently described antiviral activity [ 23 , 24 , 25 , 40 ] but also their evolutionary-conserved antibody-like activities [ 15 , 67 , 68 , 69 ]. In addition, the upregulation of this type of genes in rag1 −/− mutants has been associated with epigenetic reprogramming [ 70 ], similar to the underlying mechanisms regulating innate trained immunity [ 71 , 72 ], and apparently also occurring in the crp genes in zebrafish [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to what is observed in homozygous rag1 mutant zebrafish, which are more resistant to infection with SVCV compared to WT fish 31,32 , no significant differences in survival were found between the WT and rag1 -heterozygous fish after SVCV challenge (Supplementary Fig. S1).…”
Section: Resultsmentioning
confidence: 58%
“…This is the case for the rag1 −/− zebrafish mutant, which is a T and B cell-deficient model, and as a consequence, these animals rely exclusively on their innate immunity 43 . It was previously reported that, under naïve conditions, adult homozygous rag1 −/− fish possess enhanced innate immunity to compensate for the absence of adaptive immunity, and these fish have been shown to be more resistant to SVCV compared to WT fish 31,32,44 . In this study, when we analyzed the survival rates of WT and heterozygous rag1 +/− mutants after challenge with SVCV, we did not observe significant differences in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A similar response was previously observed for mutant rag1 −/− zebrafish. These animals do not possess adaptive immunity but show a higher basal innate immunity, including an increased pro-inflammatory status [ 70 , 71 ]; however, after SVCV challenge, the expression of some pivotal pro-inflammatory genes was lower than what was observed in the WT zebrafish [ 70 ].…”
Section: Discussionmentioning
confidence: 99%